Manajemen Bandwidth Dengan Mikrotik Untuk Mengoptimalisasi Akses Jaringan Pada Kantor Gubernur Sumatera Utara - Gita Aulia; Nabila Intan Zahrani; Muhammad Ikhsan; Muhammad Iqbal Nahwi (Journal Of Informatics And Busisnes, 2024)
Almost all areas of life use the internet network as a support for work and a medium for exchanging information. Bandwidth problems are the most frequently encountered problems in computer network technology. The lack of available bandwidth capacity has a big impact on the speed of access to the internet. The Office of the Governor of North Sumatra is a government office under the central government of the Republic of Indonesia which is located in the capital of North Sumatra Province, namely Medan City and is tasked with accommodating administrative activities carried out by the Governor and his deputies along with the regional secretariat in carrying out their duties to serve the people of North Sumatra and in connection with the central government. . The aim of this research is to optimize network access with bandwidth management using a microtic approach at the office of the Governor of North Sumatra to ensure easy and fast access to exchange information between agencies in North Sumatra and between the office of the Governor of North Sumatra and the Central Government. This research began by determining the problems associated with the use of local networks in the North Sumatra governor's office. Problem identification is carried out by understanding the needs and challenges that arise in managing internet access in the agency, especially related to constraints on the local network and uncontrolled external networks. From the trial results of bandwidth management using the Mikrotik approach at the office of the Governor of North Sumatra, it can be concluded that bandwidth management using the Mikrotik approach was successful. Bandwidth Limiter testing using the PRTG Bandwidth Network test application resulted in the highest download bandwidth at 11693 Kbit/s.